Training on the use of e-commerce to MSMEs in Kayo Batu Village, Jayapura City - Evanita Veronica Manullang; Marla Sheilamita Shalin Pieter; Meity Luisa Halena Lado; Susi Marianingsih (Community Empowerment, 2022)
One of the villages in Jayapura City is Kampung Kayo Batu, which provides a variety of MSME products. The marketing and sales of MSME products are still performed in the traditional way. According to this, MSME performers still receive a limited amount of income. Knowing how information and communication technology (ICT) is used is important for expanding product marketing and sales. This community service activity aims to help MSME actors use ICT in promoting and marketing their products. The method applied in this activity includes socialization and training on the use of social media and e-commerce for promoting MSME products in Kayo Batu Village. The result obtained from the program is the actors receive a new understanding which encourages to start promoting their products online through e-commerce and social media.